Investigating the Lyman photon escape in local starburst galaxies with the Cosmic Origins Spectrograph★. Issue 1 (26th April 2018) - Hernandez, Svea; Leitherer, Claus; Boquien, Médéric; Buat, Véronique; Burgarella, Denis; Calzetti, Daniela; Noll, Stefan
Abstract: We present a study of seven star-forming galaxies from the Cosmic Evolution Survey observed with the Cosmic Origins Spectrograph (COS) onboard the Hubble Space Telescope ( HST ). The galaxies are located at relatively low redshifts, z  ∼ 0.3, with morphologies ranging from extended and disturbed to compact and smooth. To complement the HST observations, we also analyse observations taken with the Visible Multi-object Spectrograph (VIMOS) on the Very Large Telescope (VLT). In our galaxy sample, we identify three objects with double peak Lyman-α profiles similar to those seen in Green Pea compact galaxies and measure peak separations of 655, 374, and 275 km s −1 . We measure Lyman-α escape fractions with values ranging between  5 per cent and 13 per cent. Given the low flux levels in the individual COS exposures, we apply a weighted stacking approach to obtain a single spectrum. From this COS combined spectrum, we infer upper limits for the absolute and relative Lyman continuum escape fractions of $f_{\rm abs}(\rm LyC)$  = 0.4$^{+10.1}_{-0.4}$  per cent and $f_{\rm res}(\rm LyC)$  = 1.7$^{+15.2}_{-1.7}$ per cent, respectively. Finally, we find that most of these galaxies have moderate ultraviolet and optical star formation rates (SFRs) (SFRs ≲10 M⊙  yr −1 ).